Interpreting the Bible as Bible - Wilken, Robert Louis (Journal of theological interpretation, 2010)
Modern historical criticism has disengaged understanding of the Bible from the long Christian tradition of interpretation, severing the bond between text and reader, between Scripture and the living church tradition. As a consequence, patristic and medieval interpreters are dismissed as serious commentators on the Holy Scriptures. This essay offers examples from classical Christian exegetes that illustrate how reading the Scriptures from within rather than against tradition deepens our understanding of the Bible.